ANALISIS DETERMINAN TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN DAN KOTA JAWA BARAT TAHUN 2018 - 2021 - Laia, Jemima Pricella; Ashar, Khusnul (Journal of Development Economic and Social Studies, 2023)
Unemployment can pose both a problem and a threat to the process of economic development,as it hinders individuals from fulfilling their basic needs as the inability to secure a job. Various factors contribute to this condition, and thus, this research aims to explore the impact of Mean Years of School, Number of People, Minimum Wage, and Economic Growth on the Open Unemployment Rate in 27 Regencies and Cities in West Java from 2018-2021. This study utilized secondary data and panel data regression analysis through the statistical application Eviews 12. The results indicated that Mean Years of School has a significant effect, whereas Minimum Wages, Economic Growth , and Number of People had no significant impact on the Open Unemployment rate in the Regencies and Cities of West Java.